Measuring project performance with value-based methods - Petravičius, Tomas (Business: Theory and Practice, 2008)
The value of the company is the benefit of positive net present value projects which give better return than the cost of invested capital. It is important for investors and shareholders to choose the optimal collection of strategic decisions and evaluate the performance of project realization, to measure yearly actions of managers to create shareholder value. value-based methods are used to measure the performance of projects with the objective to create the value of company. After grouping of valuation methods depending on cash flow, balance and market value, their useful adjustment to controlling performance for specific needs of investors in performed. In the paper the approach to project yearly performance management is discussed to control the value of enterprise, with benefits and limitations formulated in conclusions.Article in Lithuanian. Projekto veiklos efektyvumo matavimas vertės metodaisSantrauka. Straipsnyje, be dažniausiai taikomos finansinės analizės, analizuojamos vertės valdymo metodų taikymo projektams galimybės pagal įmonės vertės koncepciją. Pateikiama vBM metodų klasifikacija remiantis pinigų srautais, turto balansine ir  rinkos  verte,  rodiklių  ir  metodų  taikymo  ypatumai  atliekant  vertinimą  priklausomai  nuo  konkrečių  investuotojų  tikslų. Darbe apžvelgiami esminiai projekto veiklos efektyvumo metodų taikymo būdai valdant įmonės vertę ir suformuluotos su jų trūkumais ir privalumais susijusios išvados.Reikšminiai žodžiai: projektas, vertės valdymo metodai, ekonominis pelnas (EP), ekonominė pridėtinė vertė (EvA), rinkos pridėtinė vertė (MvA), pinigų srautų grąža investicijoms (cFROI), pinigų srautų pridėtinė vertė (cvA), akcininkų pridėtinė vertė (SvA), likutinis pelnas (RI).First published online: 22 Dec 2008